Modelling of chemical species of Al, Mn, Zn, and Pb in river body waters of industrial areas of West Rhodope Mountain, Bulgaria - Rabadjieva, Diana; Kovacheva, Antonina; Tepavitcharova, Stefka; Ilieva, Radost; Gergulova, Rumiana; Vladov, Ivelin; Karavoltsos, Sotirios (Environmental monitoring and assessment, 2021)
The assessment of the ecological status of natural surface water, in terms of dominant trace metals, within an area subject to various sources of pollution including a non-ferrous metal ore mining, such as the West Rhodope Mountain, Bulgaria, is significant. The present study estimates the ecological status of river body waters at industrial areas of the West Rhodope Mountain, Bulgaria, simultaneously evaluating the possibility of state forecasting, together with assessing the potential risks, through the study of scenarios focusing on (i) possible variations of physicochemical parameters such as pH, concentration levels of trace metals, sulphates, and dissolved organic carbon (DOC) of surface water and (ii) consideration of potential spontaneous precipitation reactions in the studied waters. The ecological status of river body waters was assessed through a combination of experimental field, laboratory, and computational techniques. Al, Mn, Zn, and Pb were found to be the dominant pollutants with a variety of chemical species and distribution. The most significant difference characterizing the chemical species distribution in light of total spontaneous crystallization in the systems was found for Pb, followed by Zn and Mn, with the differences being more significant at lower trace metal levels. The calculated species were discussed on the basis of HSAB (hard and soft acids and bases) principle.